2022
DOI: 10.3390/ijerph191811178
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Metals and Metalloids in Infant Formulas Marketed in Brazil, and Child Health Risks According to the Target Hazard Quotients and Target Cancer Risk

Abstract: Children are highly vulnerable to chemical exposure. Thus, metal and metalloid in infant formulas are a concern, although studies in this regard are still relatively scarce. Thus, the presence of aluminum, arsenic, cadmium, tin, mercury, lead, and uranium was investigated in infant formulas marketed in Brazil by inductively coupled plasma mass spectrometry, and the Target Hazard Quotients (THQ) and Target Cancer Risk (TCR) were calculated in to assess the potential risk of toxicity for children who consume the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, one sample exceeded the Cd limit (0.24 mg/kg), and two samples exceeded the Pb limit (0.62 and 0.84 mg/kg). Comparing our mean concentrations of Pb (20.36 µg/kg) and Cd (3.72 µg/kg) with other studies, we found them to be lower than those in Lebanon (mean: Pb: 371 µg/kg; Cd: 255 µg/kg) (Elaridi et al., 2021) but higher than levels reported in China (Beijing, mean: Pb: 2.03 µg/kg; Cd: 0.98 µg/kg; southern China, Pb: 7.76 µg/kg; Cd: 0.97 µg/kg) (Lin et al., 2022; Su et al., 2020), Turkey (mean: Pb: 25.4 µg/kg; Cd: 2.172 µg/kg) (Başaran, 2022), and Brazil (mean: Pb: limit of quantification (LOQ: 10 µg/kg) to 3.6 ± 4.1 µg/kg; Cd: LOQ (2 µg/kg) to 8 ± 3 µg/kg) (de Almeida et al., 2022) (Table S1). Notably, the study underscores the importance of monitoring and adherence to regulatory standards to ensure the safety of infant formula products in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…However, one sample exceeded the Cd limit (0.24 mg/kg), and two samples exceeded the Pb limit (0.62 and 0.84 mg/kg). Comparing our mean concentrations of Pb (20.36 µg/kg) and Cd (3.72 µg/kg) with other studies, we found them to be lower than those in Lebanon (mean: Pb: 371 µg/kg; Cd: 255 µg/kg) (Elaridi et al., 2021) but higher than levels reported in China (Beijing, mean: Pb: 2.03 µg/kg; Cd: 0.98 µg/kg; southern China, Pb: 7.76 µg/kg; Cd: 0.97 µg/kg) (Lin et al., 2022; Su et al., 2020), Turkey (mean: Pb: 25.4 µg/kg; Cd: 2.172 µg/kg) (Başaran, 2022), and Brazil (mean: Pb: limit of quantification (LOQ: 10 µg/kg) to 3.6 ± 4.1 µg/kg; Cd: LOQ (2 µg/kg) to 8 ± 3 µg/kg) (de Almeida et al., 2022) (Table S1). Notably, the study underscores the importance of monitoring and adherence to regulatory standards to ensure the safety of infant formula products in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…Total target hazard quotient of geophagic soils collected from selected local markets was obtained by adding target hazard quotient of each hazardous substance. The later was calculated according to Nkansah et al [38] , Chien et al [11] and Kortei et al [29] , Pokorska-Niewiada et al [42] , de Almeida et al [14] and Ain et al [2] . Total hazard quotient value greater than 1 indicates that potential health risk may occur upon exposure and when it is less than 1 indicates no substantial health effects that may arise upon exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Cancer risk was achieved by summing the risks of each carcinogenic metal. where;CR=Cancer risk, EFr = Exposure frequency, EDtot = Exposure duration, IngR = Soil ingestion rate, C = Heavy metal concentration (mg/kg), Bw = Average adult body weight, CanSF = Cancer slope factor of hazardous substances (mg/kg/day), ATn = Average exposure for non-carcinogens 365 days/year x Number of exposure years (70 years) Kortei et al [29] , (Pokorska-Niewiada et al [42] , de Almeida et al [14] and Ain et al [2] Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Essential mineral concentrations (Na, K, Mg, Mn, P and Zn) were determined according to Almeida et al [ 10 , 34 ] by inductively sequential coupled plasma optical emission spectrometry (ICP-OES) with a radial view on a Horiba Jobin Yvo Ultima 2 ICP-OES (Longjumeau, FRA), equipped with a cyclonic nebulization chamber, MiraMist type nebulizer (Mira Mist CE, Burgener Research Inc., Mississauga, ON, CAN) and automatic AS 421 sampler model. Instrumental ICP-OES conditions are included in the Supplementary file—Table S2 .…”
Section: Methodsmentioning
confidence: 99%